Legal Protection Against Under Cover Buys in Exposing Narcotics Trafficking - Jekson Kipli Lumban Toruan; Herlina Manullang; Jinner Sidauruk (PT FORMOSA CENDEKIA GLOBAL, 2025)
The phenomenon of narcotics circulation that is increasing today requires a special investigative approach, one of which is the application of under cover buy. However, the implementation of under cover buys presents a high risk for the National Police who carry it out, so comprehensive legal protection is needed. This study aims to analyze the form of legal protection provided to the National Police that acts as an under cover buy, its implementation mechanism, and the obstacles faced in providing such protection. This study uses an empirical juridical research method with a normative juridical approach. Data collection was carried out through interviews with the Medan Police Drug Investigation Unit, field observations.